Family planning desires of older adults (50 years and over) in Botswana - Njoku Ola Ama; John O. Olaomi (South African Family Practice)
Background: This study analysed the views of a stratified sample of 444 older adult women from selected health districts in Botswana on their family planning (FP) use, knowledge, accessibility and availability. Methods: Four health districts (two rural and two urban) were purposively selected. The sample of 444 older adults was proportionally allocated to the districts. The snowball technique was used in identifying older adults from each district. Results: Contraceptive prevalence among the older adults is low (25. 2%); ever used rate was 23.6%, with unmet need as high as 75.2%. The traditional methods are mainly used. Knowledge, availability and accessibility of the natural methods are high. The likelihood ratio test shows that age, educational status, marital status and employment jointly significantly predicts (p 0.05) the use of FP. Conclusion: Family planning programme developers and policy-makers should develop educational interventions that will be age specific and relevant to older adults.